Application Of The Concept And Monitoring Of Robot Line Follwer As a Prototype Of Pekanbaru Trans Metro Bus Towards The Revolution Industry 4.0 (Penerapan Konsep Dan Monitoring Robot Line Follwer Sebagai Prototipe Bus Trans Metro Pekanbaru Menuju Era Revo - Anip Febtriko; Wita Yulianti (Universitas Putra Indonesia YPTK Padang, 2019)
Public transportation is a major part of developing an advanced and modern city. Progress in public transportation is needed to be planned and realized to deal with the development of the city together with population and economic growth. The use of the Trans Metro Pekanbaru bus transportation is not in line with the development and progress of the City of Pekanbaru, which wants to be a smart city, where the role of the Internet of Things (IoT) needs to be realized in building smart cities and currently the use of the Trans Metro Pekanbaru bus in Pekanbaru is still becoming a problem. it needs to be resolved like the Trans Metro Pekanbaru bus lane which still uses a shared lane which causes congestion and lack of good trafic regulations. Trans Metro Pekanbaru bus transportation is still weak in terms of arrival and departure times. Trans metro Pekanbaru has not yet been integrated in a system that can be monitored centrally through the application of an application system based on the Global Positioning System (GPS). To overcome this problem, it is necessary to have the Trans Metro Pekanbaru bus transportation in the form of a prototype line follower robot which is a solution to overcome this problem. The purpose of this research is to make the line follower robot as a trans-metro silmulation bus for Pekanbaru become a smart city that is able to serve and facilitate the public's need for public transportation towards the industrial revolution 4.0. Line follower robot is a robot that works by following a line in the form of a road such as a traf ic lane, where the robot works using photodiode sensors and ultrasonic sensors as proximity sensors so that it stops automatically at every stop or place where passengers rise and fall. Line follower robots are automatically controlled so programming code and fuzzy algorithms are needed. Line follower robots are also equipped with Closed Circuit Television (CCTV) to determine passenger conditions.